Modeling and Experimental Study on the Air Infiltration of Cold Chain Transport Equipment - Liu Guanghai; Xie Ruhe; Qu Ruigui (Zhileng xuebao)
The air infiltration though the cold chain transport equipment directly affects the safety during transport and the energy consumption. The existing standards on the cold chain transport equipment adopt the differential pressure method and the resulting value of air infiltration is difficult to characterize the actual running situation. To solve this problem, the mechanism of air infiltration through the cold chain equipment is analyzed and the relationship between the running speed, the aging conditions and the equipment status is gained. The computational model of the air infiltration through the vehicles is found and the definition method of relevant parameters such as air infiltration index and the equivalent infiltration area is gained through the experiment. The study showed that the model can reflect the air infiltration characteristics of refrigerated transport equipment well and provide a reference to the overall evaluation on the air tightness and optimal control of the vehicles.